La donna è un isola - Natkańska, Anna (Romanica Silesiana)
The woman is an island, uninhabited (soulless), inaccessible, or a predictable and well‑known. A woman who lives on the island, can perfectly reflect the entire insular nature of being. In my article I will present the form of women living in this closed environment and prove how strong stigma the island can leave in human life. Heroines all of the novel created in the twentieth century and written by writers associated with Sicily, were selected on the basis of contrast: the mother of “Sicilian conversation” by Elio Vittorini, prostitutes from the “Pension Eva” by Andrea Camilleri. The thing which determines their lives, which affects their choices and relationships to others, is an island, its history and severity, which in this article I will try to present and proove. Reflections and interpretations of texts will be preceded by presentation of interesting philosophical and sociological aspects of a woman and her social functions. Key words: islander, island, Sicily in literature, Andrea Camilleri, Elio Vittorini